Developing Flow In Microchannel Having Regular Microstructure - Tan, Yan Xu (Universiti Sains Malaysia, 2018)
Microchannel is used as compact heat exchangers or microcoolers in electronics packaging in many engineering system. The system performance depends on laminar flow development in the microchannels. Sometimes, the use of short microchannel lengths is insufficient to yield a fully developed flow. In other words, only developing flow could prevail along the channel length. Thus, it is essential to determine the distance needed for a flowing liquid before a fully developed flow condition could prevail. The main objective of the work is focused on exploring the effects of different surface topologies on the hydrodynamic entrance region in the channels. This study is carried out by using ANSYS FLUENT 16.1, a finite volume based computational fluid dynamics (CFD) software package to simulate the fluid flow in parallel plate and rectangular microchannel having regular microstructure. The data obtained from the simulation are then processed by using MATLAB to determine the hydrodynamic entrance length. As expected, regular microstructure has the effect on hydrodynamic entrance length of both increasing and decreasing the hydrodynamic entrance length of parallel plate and rectangular microchannel with its microstructure parameter of dimensionless period extent of groove-rib combination, L and no slip fraction δ.